Analisis Implementasi Teknologi Blockchain dalam Meningkatkan Transparansi, Efisiensi, dan Keamanan Transaksi Keuangan Perbankan Syariah Indonesia - Aminin, Rista Izza (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2024)
Implementing blockchain technology in the Islamic finance sector, particularly in Islamic banking in Indonesia, holds significant potential to enhance transparency, efficiency, and security in transactions. However, its application still requires further research to ensure compliance with Islamic law principles. This study aims to analyze blockchain implementation in improving transparency, efficiency, and security in Islamic banking transactions while ensuring alignment with Sharia principles. A qualitative approach with a literature review is used, examining relevant sources on blockchain applications in the Islamic banking sector. The data for this study is gathered from scholarly articles, books, and related documents. The findings suggest that blockchain can improve transparency, reduce intermediaries, accelerate transactions, and enhance security. However, the primary challenge lies in adapting to Sharia regulations, which requires collaboration between regulators, financial institutions, and technology experts. Strengthening regulations and gaining a deeper understanding of this technology will support wider adoption in the Islamic banking sector.